A competitive framework for industrial product-service systems. Issue 1 (1st February 2010) - Roy, Rajkumar; Cheruvu, Kalyan S.
In present economic development, the investment manufacturing companies are transforming to integrated product and service based companies for better value proposition, revenue generation opportunities and sustainable customer value. The context of this review is limited to business-to-business market and investment goods based industries. The present paper gives an understanding of the fundamentals of industrial product-service system (IPS²) thorough literature review. A new representation for the competitive IPS² in terms of 3-D space for successful business is presented. Various drivers for the IPS² are identified along with the desired results of any IPS². A new comprehensive framework has been explained for a competitive IPS² with sustainable customer value as the outcome. A need for future research and challenges posed by IPS² are pointed out from the research findings.